2019
DOI: 10.1055/a-0808-5003
|View full text |Cite
|
Sign up to set email alerts
|

Bedeutung der selektiven Lebensqualitätsanalyse nach Sympathikus-Clipping bei Patienten mit lokaler Hyperhidrose

Abstract: Zusammenfassung Einleitung Die Hyperhidrose (HH) geht mit einer physischen und psychischen Einschränkung einher. Die Behandlung umfasst sowohl konservative als auch operative Methoden und strebt eine dauerhafte Verbesserung der Lebensqualität (LQ) der Betroffenen an. Die endoskopische Sympathikusblockade (ESB) stellt eine etablierte operative Therapiemethode dar und gilt als ein effektives chirurgisches Verfahren bei Versagen der konservativen Therapieoptionen. Das Ziel unserer Studie war, die LQ-Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Five included studies reported on the DLQI [3,26,41,43,46]; three on the HQLQ [1,6,35], the HidroQoL [9,18,20] and the HDSS [39,46,47], respectively; two on the SF-36 [38,46], the Hyperhidrosis Disease Severity Measure-Axillary (HDSM-Ax) [16,22], as well as the Hyperhidrosis Scale (HS) [21,35]; and one each on the ASDD and its child version (ASDD-C) [34], the Hyperhidrosis Impact Questionnaire (HHIQ) [25], the Illness Intrusiveness Rating Scale (IIRS) [5], the Hyperhidrosis Questionnaire (HQ) [24], the Sweating Cognitions Inventory (SCI) [52] and the Table 3 GRADE approach for grading the quality of evidence [36] Starting point: assumption that the evidence is of high quality. Information on how to downgrade is described in the COSMIN user manual [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five included studies reported on the DLQI [3,26,41,43,46]; three on the HQLQ [1,6,35], the HidroQoL [9,18,20] and the HDSS [39,46,47], respectively; two on the SF-36 [38,46], the Hyperhidrosis Disease Severity Measure-Axillary (HDSM-Ax) [16,22], as well as the Hyperhidrosis Scale (HS) [21,35]; and one each on the ASDD and its child version (ASDD-C) [34], the Hyperhidrosis Impact Questionnaire (HHIQ) [25], the Illness Intrusiveness Rating Scale (IIRS) [5], the Hyperhidrosis Questionnaire (HQ) [24], the Sweating Cognitions Inventory (SCI) [52] and the Table 3 GRADE approach for grading the quality of evidence [36] Starting point: assumption that the evidence is of high quality. Information on how to downgrade is described in the COSMIN user manual [31].…”
Section: Resultsmentioning
confidence: 99%
“…Several PROMs that cover diverse constructs have been developed and reported in the literature for patients with hyperhidrosis, for instance, the Hyperhidrosis Quality of Life Index (HidroQoL) [20], the Hyperhidrosis Disease Severity Scale (HDSS) [47] or the Axillary Sweating Daily Diary (ASDD) [34]. In clinical research and practice, not only hyperhidrosis-specific PROMs are used but also skinspecific or more generic PROMs such as the Dermatology Life Quality Index (DLQI) [9] or the short-form health survey (SF-36) [18,38].…”
Section: Introductionmentioning
confidence: 99%